Deciphering the Possible Role of Statins as Antibacterial Agents through Molecular Modelling Approach: Role of statins as antibacterial agents - Jupudi, Srikanth; TP, Athira; Azam, Mohammed Afzal (Iranian Journal of Pharmaceutical Sciences, 2021)
The global incidence of resistance to commonly used antibiotics was a challenging public health concern that justifies the urgency in developing novel antibacterial agents. ATP-dependent Mur ligases (MurC, MurD, MurE, and MurF) are validated targets in antibacterial drug design. Drug repurposing or drug repositioning is an alternative strategy in identifying new indications for the currently approved drugs. Statins are currently FDA-approved drugs used to treat hyperlipidemia. The pleiotropic effects of statins, along with their anticipated antibacterial properties, encouraged us to investigate them against MurD ligase of Escherichia coli and Staphylococcus aureus. The molecular docking and MMGB-SA studies revealed that amongst all selected statins, pravastatin exhibited higher binding affinity with the catalytic residues of Escherichia coli (-7.24 kcal/mol and -88.36 kcal/mol) and Staphylococcus aureus (-7.47 kcal/mol and -63.75 kcal/mol) MurD ligases. Further, 20 ns MD simulation showed stability and favorable interaction pattern of pravastatin with both enzymes.